Prediction of oral diseases in care dependent older people - Christina Andersen; Astrid Pernille Jespersen; Kim Ekstrand; Esben Boeskov Øzhayat (BMC Oral Health)
Abstract Background A large number of older people depend on others for help with their daily personal care, including oral health care. Nursing home and elder-care staff often face challenges identifying older people, who are exposed to or at an increased risk of oral diseases. Thus, the aim of this study was to identify risk factors that non-dental care staff can use to identify older people at risk of oral diseases and poor oral hygiene. Methods In this cross-sectional study, the oral health and risk factors for poor oral health were determined for 217 care dependent older people living in two nursing homes and a rehabilitation centre or receiving home care in two Danish municipalities. The outcome variables for oral disease i.e. caries, periodontitis, and gingivitis, and oral hygiene, i.e. plaque and calculus, were assessed using standardised oral examinations. Risk factors for oral diseases and poor oral hygiene were assessed based on a questionnaire concerning (1) background information, (2) health status, (3) social support, (4) oral health behaviours, and (5) self-reported oral health. The associations between oral health and risk factors were investigated using logistic regression analyses. Results In general, older people with different living arrangements had quite similarly distributed risk factors. The oral examinations showed that 54.5% had oral diseases, and 14.8% had poor oral hygiene. Not seeing a dentist regularly was significantly associated with having oral diseases (Odds Ratio, 2.87; CI, 1.53–5.39) and poor oral hygiene (OR, 4.50; CI, 1.83–11.05). A significant association was found between the presence of an oral disease and adversely affected quality of life (OR, 2.65; CI, 1.42–4.95), especially due to challenges eating (OR, 3.76; CI, 1.64–8.60) and/or smiling and showing teeth (OR, 3.64; CI, 1.27–10.42). A significant association was also found between poor oral hygiene and taking psychotropic drugs (OR, 2.61; CI, 1.08–6.30). Conclusion Questions regarding the use of the dental care system and oral health problems could be used by nondental care staff in conversations with older people to determine their risk of oral diseases and poor oral hygiene.